1997
DOI: 10.1002/art.1780400516
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of bacterial arthritis. A prospective community‐based study

Abstract: Objective. To assess the outcome and adverse prognostic factors of bacterial arthritis (BA). Methods. In a prospective community survey of BA, data were collected at the time of diagnosis and at a mean of 2 years later. A poor patient outcome was defined as death due to BA or severe overall functional deterioration. A poor joint outcome was defined as amputation, arthrodesis, prosthetic surgery, or severe functional deterioration. Possible prognostic factors were analyzed by univariate analysis. Results. BA wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
94
0
8

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(112 citation statements)
references
References 44 publications
3
94
0
8
Order By: Relevance
“…According to one report septic arthritis has an annual incidence of two to 10 per 100,000 individuals, although that study did not report data on the incidence of ankle septic arthritis [6]. Untreated joint infection can lead to irreversible destruction of articular cartilage, disability, systemic sepsis and death [3,4,7]. A retrospective study of septic arthritis in the United Kingdom reported 23.8% of patients had considerable loss of function in the affected joint and 11.5% of patients died as a result of their illness [18].…”
Section: Introductionmentioning
confidence: 99%
“…According to one report septic arthritis has an annual incidence of two to 10 per 100,000 individuals, although that study did not report data on the incidence of ankle septic arthritis [6]. Untreated joint infection can lead to irreversible destruction of articular cartilage, disability, systemic sepsis and death [3,4,7]. A retrospective study of septic arthritis in the United Kingdom reported 23.8% of patients had considerable loss of function in the affected joint and 11.5% of patients died as a result of their illness [18].…”
Section: Introductionmentioning
confidence: 99%
“…If treatment is delayed, septic arthritis has a mortality rate between 5% and 15 % often as a result of septic shock [4]. Septicemia is a known complication resulting from the transient or chronic bacteremia associated with most cases of septic arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Septicemia is a known complication resulting from the transient or chronic bacteremia associated with most cases of septic arthritis. [4] However, such deaths usually have a more progressively deteriorating course rather than a sudden deterioration of seemingly improving condition. Sudden deterioration of her condition points towards pulmonary thrombo embolism; another well known complication of septic arthritis [5].…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative risk factors include woundhealing complications (e.g., superficial infection, hematoma, delayed healing, wound necrosis, and dehiscence), atrial fibrillation, myocardial infarction, urinary tract infection, prolonged hospital stay, and S. aureus bacteremia [12][13][14][15], [18][19][20][21]. An increased rate of infection occurs in the pre-damaged joint and is also associated with particular predispositions of the patients (Table 1) [22][23][24]. In articular, a joint prosthesis is a high risk predisposition for an infection.…”
mentioning
confidence: 99%